QUESTIONS OF PHILOSOPHY AND SCIENCE IN THE WORKS OF V. I. VERNADSKY - L. A. Pafomova; R. V. Fedorov (Дискурс)
The article considers the formation of the concept of scientific worldview and its characteristics. The principles and patterns of the development of science proposed by V. I. Vernadsky are analyzed. It is shown that his approach to this process can be a source of methodological reflection in the modern philosophy of science. Particular attention is given to the methodology of V. I. Vernadsky's views, particularly to the fact that science and philosophy should not contradict each other, and on the contrary, they should complement each other. The special status of scientific knowledge is emphasized, where, on the one hand, there exists a real need to cover all the variety of scientific concepts, facts, etc., and on the other hand, there is no such expert who, while being a scientist, would have an expert knowledge on these diverse subjects.